Coexistence and Non-violence: From Urdu Poetry's Perspective - Anjum, Naila; Razzaq, Noreen (sourcecoder, 2023)
A human society is a social unit comprised of the connections between individuals, established through mutual resources and shared objectives. The foundation of an Islamic society is built upon the principles of mutual welfare and benefit. The requirement for coexistence is the formation of a society where there is no trace of oppression, injustice, or inequality. Urdu poetry conveys the message that a peaceful and non-violent environment supports the better development of human life. This paper highlights how poets have determined the right direction for the journey of human evolution, raised awareness of human rights, and made sincere efforts for their implementation.